Production Principles in Islam: A Review of Canned Food Products - Tartila, Muzayyana; Tahiyati, Azka (Indo Consultan Energi, 2023)
Production is a consumption chain which provides goods and services that constitute a consumer need. Production activities are divided into two types within the framework of Islamic economic activity. The first is someone who wants to carry out production activities and only wants to get the maximum profit without paying attention to the aspects stated in Islam. The second is someone who wants to carry out production activities to increase the welfare of humankind on earth by paying attention to the elements of production that have been determined in Islamic law. This research was conducted using a descriptive method with a qualitative approach. The results of this study indicate that the production principles that a producer must carry out in canned food products must include five aspects. First, the focus of monotheism in production activities is the realisation of a production that is produced in the form of products that are halal toyyiban and protected from elements that harm. Second, on the principle of humanity, it is recommended that humankind can prosper on the earth and cover all aspects that exist on earth. Third, the form of implementation of the principle of justice in production activities means that producers can enforce rights, obligations, and responsibilities towards consumers. Fourth, in Islam, one form of the principle of benevolence, producers in their production activities are oriented not only to profits but also to the blessings obtained from profits, namely by paying attention to several aspects of their products. Fifth, on the principle of freedom and responsibility, humans are free to carry out any production activity as long as it does not go outside the corridors of Islamic law and does not harm others. They can be held accountable if something undesirable happens to consumers.